2006
DOI: 10.1111/j.1439-037x.2006.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotype × Environment Interactions in Chinese Spring Wheat by the AMMI Model, Correlation and Path Analysis

et al.

Abstract: An understanding of the characteristics of crop varieties and advanced lines could help improve their cultivation and to further enhance their potential. The objectives of this study were to estimate the genotype (G), environment (E) and genotype · environment (GE) interactions on the grain yield of Chinese spring wheat genotypes in 2000 and 2001 by the additive main effects and multiplicative interaction (AMMI) model, and to evaluate the relationships between yield and its components by correlation and path a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
(43 reference statements)
1
25
0
1
Order By: Relevance
“…Some researchers studied correlation coeffi cients of various grain yield components with grain yield of bread wheat for its genetic improvement (Uddin et al, 1997;Aycecik and Yildirim, 2006;Akram et al, 2008). Several researchers reported that wheat grain yield was positively correlated with 1000 seed weight (Li et al, 2006;Akram et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers studied correlation coeffi cients of various grain yield components with grain yield of bread wheat for its genetic improvement (Uddin et al, 1997;Aycecik and Yildirim, 2006;Akram et al, 2008). Several researchers reported that wheat grain yield was positively correlated with 1000 seed weight (Li et al, 2006;Akram et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation and path analysis of yield components are useful tools to determine valuable genotypes (Li et al, 2006). Path analysis is a reliable statistical method, which provides tool to quantify the interrelationship of various grain yield components and indicate whether the infl uence is directly refl ected in the grain yield or take some other path ways to produce an eff ect.…”
Section: Introductionmentioning
confidence: 99%
“…The graphic presentation of genotype and environment AMMI analysis values facilitates the visual evaluation of genotype and environment behaviour (Kaya et al, 2002;Li et al, 2006). The layout of the environments and restorer lines on the individual AMMI1 and AMMI2 biplots of the cms lines exhibited considerable differences, confirming the existence of interactions between the environments and hybrid combinations.…”
Section: Resultsmentioning
confidence: 99%
“…The results of AMMI analysis can be graphically presented in biplot form, which shows the main additive effects and interaction effects for all the genotypes and environments (Gabriel, 1971;Yan and Tinker, 2005;Gauch, 2006;Li et al, 2006;Krizmanić et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…モデル (Bradu andGabriel 1978, Gauch 1988, Gauch and Zobel 1988)では,いくつかの安定性指標値が提唱され, 品種における形質の安定性評価に用いられている (Zhang et al 1998a, 1998b, Purchase et al 2000, Li et al, 2006, Farshadfar 2008, Farshadfar et al 2011) .また,遺伝子型の 効果を調整し, 主成分分析の可視化手段であるバイプロッ トの理解が容易な GGE バイプロットモデル (Gabriel 1971, Yan andKang 2003)は,よく用いられている手法で ある.これらの手法は,収量形質の安定性評価のために 考案され,用いられてきたが (Crossa 1990, 1991, Yan and Kang 2003) ,現在まで広範な農業形質 への応用例が報告されている (Zhang et al 2003, 八城ら 2004,Mohammadi et al 2011, Thangavel et al 2011 …”
unclassified